Identification and characterization of CONSTANS-like (COL) gene family in upland cotton (Gossypium hirsutum L.). - Darun Cai; Hui Liu; Na Sang; Xianzhong Huang (PLoS ONE)
The CONSTANS/FLOWERING LOCUS T (CO/FT) regulon plays a central role in the control of flowering time in photoperiod-sensitive plants. Flowering time in wild cotton (Gossypium spp.) has strict photoperiod sensitivity, but domesticated cotton is day-neutral. Information on the molecular characterization of the CO and CO-like (COL) genes in cotton is very limited. In this study, we identified 42 COL homologs (GhCOLs) in the G. hirsutum genome, and many of them were previously unreported. We studied their chromosome distribution, phylogenetic relationships, and structures of genes and proteins. Our results showed that GhCOLs were classified into three groups, and 14 COLs in group I showed conserved structure when compared with other plants. Two homoeologous pairs, GhCOL1-A and GhCOL1-D in Group I, showed the highest sequence similarity to Arabidopsis thaliana CO and rice CO homologous gene Heading date1 (Hd1). Tissue-specific expression showed that 42 GhCOL genes may function as tissue-specific regulators in different cells or organs. We cloned and sequenced the 14 GhCOL genes in Group I related to flowering induction to study their diurnal expression pattern, and found that their expression showed distinct circadian regulation. Most of them peaked at dawn and decreased rapidly to their minima at dusk, then started to accumulate until following dawn under long- or short-day conditions. Transgenic study in the Arabidopsis co-2 mutant demonstrated that GhCOL1-A and GhCOL1-D fully rescued the late-flowering phenotype, whereas GhCOL3-A, GhCOL3-D, GhCOL7-A, and GhCOL7-D partially rescued the late-flowering phenotype, and the other five homoeologous pairs in Group I did not promote flowering. These results indicate that GhCOL1-A and GhCOL1-D were potential flowering inducers, and are candidate genes for research in flowering regulation in cotton.